A relationship-focused investigation of spousal psychological adjustment to dual-sensory loss. (4th March 2018) - Lehane, Christine M.; Elsass, Peter; Hovaldt, Hanna B.; Dammeyer, Jesper
ABSTRACT: Objectives: The relationship intimacy model of psychosocial adjustment to illness indicates that a patient's willingness to communicate about their illness, as perceived by the spouse, is a strong predictor of spouse relational and psychological well-being. Inspired by the relationship intimacy model, the current study examined the psychological adjustment of spouses of individuals with dual-sensory loss (DSL), a disability where interpersonal communication is of particular concern. Method: Surveys were sent to all known individuals and their partners who were 50 years of age or older and were enrolled in services for acquired DSL in Denmark. A total of 65 spouses met the inclusion criteria of which 45 (69%) returned a partner survey. Results: Results showed a significant association between couples' sensory loss-related communication, relationship satisfaction, perceived support and psychological well-being. Perceived support significantly mediated the association between couples' sensory loss communication and spouse psychological well-being. Conclusion: The current study's findings provide support for a relationship-focused perspective of spousal psychological adjustment in the context of DSL. Further, couples' sensory loss-related communication is presented as a potential intervention target to enhance spouse perceived support and psychological well-being.